Characteristics and factors associated with the position of the haptic after ICL V4C implantation. Issue 4 (April 2023) - Tan, Weina; Chen, Qian; Yang, Ruibo; Wang, Zheng; Zeng, Qingyan; Lei, Xiaohua; Jin, Lina; Zhao, Shaozhen
Abstract : This article use an ultrasound biomicroscopy image to quantitatively assess the position of ICL haptic and found the ICL haptic-related parameters have an important influence on the clinical vault. Abstract : Purpose: To assess the position of implantable collamer lens (ICL) haptic after ICL V4C implantation using standardized panoramic ultrasound bimicroscopy (UBM), to analyze its characteristics, associated factors, and the relationship with the clinical vault quantitatively. Setting: Hankou Aier Eye Hospital, Wuhan, Hubei, China. Design: Cross-sectional study. Methods: 167 subjects (323 eyes) implanted with ICL V4C who had a 3-month follow-up with UBM examination were included in this study. The relative position of ICL to the adjacent structure and ICL haptic-related parameters (the final tip point of ICL haptic [ftICL haptic], measured from the scleral spur to the final tip of the ICL haptic, the posterior of the ICL to ICL haptic [ICL arc], measured from the posterior surface of the ICL to the ICL haptic plane, and the height of the crystalline lens from the ICL haptic (lens arc), measured from the anterior surface of the crystalline lens to the ICL haptic plane and other parameters), were estimated on the UBM image. Eyes were divided into 3 subgroups according to the ftICL haptic (Group 1: ≤0.5 mm; Group 2: 0.5 to 1.0 mm; and Group 3:≥1.0 mm, respectively), and the factors associated with the ICL haptic-related parameters and their impact on the clinical vault were evaluated. Results: The haptics could be imaged in the ciliary sulcus, on the ciliary body, and under the ciliary body in 629 (48.7%), 525 (40.6%), and 138 (10.7%) eyes, respectively. The ftICL haptic and the summation of ICL arc and lens arc showed a correlation with the clinical vault ( r = −0.34, P = .00; r = 0.87, P = .00). When the ftICL haptic results were divided into 3 groups, the percentage of eyes that exhibited clinical vault >750 μm were lowest in Group 3. Multivariate regression analysis showed spherical equivalent, white-to-white (WTW), anterior chamber volume (ACV) and iris–ciliary angle (ICA); the difference between the implanted ICL size and horizontal sulcus-to-sulcus (ICL size-STS) were associated with the ftICL haptic. The IOP, WTW, ACV, and the ICL size-STS were significantly associated with ICL arc, while the ICA and lens rise were associated with lens arc. Conclusions: The position of ICL haptic was associated with the clinical vault. Its quantitative evaluation may provide valuable information to help clinicians to select the best ICL size before surgery and understand the formation of clinical vault after surgery.